(untitled) (Research, Society and Development, 2021)
Given the above, this study aims to understand the purpose of nurses in the Pap smear: obstacle and women’s perception, in order to achieve and demonstrate the importance of the Pap smear. Method: Integrative review carried out in September 2021 in the online databases BDENF and LILACS in the period from 2008 to 2021. For the research, we used the descriptors “Nurse” and “Pap examination” with the word- “Perception” key, using the “AND” between the words. 115 articles were found, 54 from BDENF and 61 from Lilacs, 12 were selected and 103 were excluded, with the association of descriptors. Results: the results show that there are many factors that contribute to the non-adherence of women to the Pap smear, for example; fear of bodily exposure, male professional, lack of knowledge of the severity of cancer and the importance of screening, among other factors, in addition to showing that nurses can and should be present in the rupture of such paradigms. It is concluded, therefore, that for women to adhere to the exam, an important strategy and an active search is important, as well as strengthening the bond and adopting measures such as health education for the construction of the necessary knowledge for women.